Conceptual model of cost-benefit analysis for monetary and non-monetary items in industrialised building system (IBS) project - Siti Nur Atikah Abd Rashid,; Natasha Khalil,; Haryati Mohd Isa, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Industrialised Building System (IBS) is known as a construction system that consists of a combination of components manufactured either on-site or off-site then positioned and assembled into structures. Among the benefits of IBS construction includes labour cost reduction, support desirable environment; maximize efficient use of resources and waste minimisation towards sustainable construction. However, the Malaysian construction industry still has a low take-up rate on IBS construction. The benefits of IBS are more reliable to be presented in a tangible (monetary) value and intangible (nonmonetary) basis rather than descriptive benefits. Hence, to promote the project's viability via IBS, Cost-Benefit Analysis (CBA) can be used to identify the soft issue or non-direct cost and elicits more transparency in IBS projects. This paper presents the conceptual review of the fundamental theory of CBA on the measurement of cost and benefits that can be converted as a weighing impact for an IBS project. An initial conceptual model known as CBA-IBS model is proposed as an approach that a decision maker can use to find the balance between the amount of effort invested in the initial cost of IBS construction and the realised revenues. This study concluded that CBA is able to foster the viability of IBS in more comprehensive criteria of monetary and non-monetary benefits.